How language works in politics : the impact of vague legislation on policy - Williams, Matthew (Policy Press, 2018)
Using analysis from machine readings of all legislation enacted between 1900 and 2015, this text discusses the social impact increasingly elastic legislative language on the contemporary workings of the British constitution.